Penerapan Metode Prototype Pada Sistem Informasi Pengelolaan Data Tamu Hotel - Dody Pria Sagita; Alam Supriyatna (Sekolah Tinggi Ilmu Komputer Binaniaga, 2021)
The management of guest data at Hotel Gerbera is currently still by recording books, starting from the check-in process which is done by filling out the registration sheet, then inputting guest data who has checked in in the Guest In The House data table using Microsoft Excel and writing money data. Incoming cash payments, debit / credit and receivables per shift in the Daily Cashier Sheet. This kind of data input process is less effective because it takes a lot of time to enter guest data into each different report form. The research with the title